A Low-Cost Microwave Hybrid Biosensor for Glucose Concentration Sensing - Köse, Umut; Kartal, Mesut (IEEE, 2024)
This study uses a hybrid biosensor consisting of a patch antenna with a defected ground plane and a frequencyselective surface (FSS) to detect glucose concentration in the microwave frequency region. The sensing mechanism is based on identifying the relative permittivity and loss tangent variations caused by different ratios of glucose-distilled water solutions placed in the area of the sample under test (SUT). This study tested four glucose-distilled water solutions in the SUT region: 72 mg/dL, 216 mg/dL, 330 mg/dL, and 600 mg/dL. The Debye model is utilized to ascertain the dielectric characteristics of the solutions. When the volume percentage of glucose in the glucose-deionized water solutions in the SUT increased from 72 mg/dL to 600 mg/dL, a frequency shift of 44 MHz was observed in the resonance frequency of the hybrid sensor called Sensor 1. To show the effect of mutual coupling between the defected ground plane and the FSS on sensitivity parameters in the hybrid sensor structure, a new sensor called Sensor 2 was designed. Sensor 2 has the same geometry and dimensional parameters as Sensor 1 but only consists of a patch antenna with a defected ground plane. A frequency shift of 7 MHz was noted in the resonance frequency of Sensor 2 when the volume percentage of glucose in the glucose-deionized water solutions in the SUT increased from 72 mg/dL to 600 mg/dL. According to the simulation results, the sensitivity of Sensor 1 was calculated as 83.333 kHz/mg dL-1, while Sensor 2 was 13.258 kHz/mg dL-1. Thus, it is shown that FSS can be used in antenna-based sensor structures for sensitivity improvement.
Keywords: Hybrid Biosensor; Non-Invasive Sensor; Microstrip Antenna; Frequency Selective Surfaces (FSS)